Adequate Crown Preparation for Porcelain Fused to Metal Csrowns Among Practitioners of Hyderabad (Medical Forum Monthly, 2020)
Objective: To determine the frequency of adequate crown preparation for porcelain fused to metal crowns among local practitioners.Study Design: Descriptive study.Place and Duration of Study: This study was conducted in clinics of private practioners and public sector hospitals of Hyderabad city from January to August 2018.Materials and Methods: Data was collected from dies’ of tooth prepared for porcelain fused to metal crowns; dies were collected from different clinics. Data was collected from die trimmed the plaster models after the delivery of porcelain fused to metal crowns to patients. Dies were stabilized in wax blocks, pictures were snapped in buccal and mesial view for convergence angles measurement and tooth placed with scale for height measurement. The pictures were processed through latest version of AUTOCAD software. All the data was entered in proforma. The data was analyzed by SPSS version 22.0. Chi square test was applied for checking the statistical difference.Results: Males were 65% and females were 35%. General practitioners were 41%, P.G students were 48% and consultants were 11%. The mean Bucco-lingual convergence angle of dies was 25.79± 9.569. Mean Mesio-distal convergence angle of dies was 20.72 ± 7.180 and mean Height of dies was 5.789 ± 2.0165. Adequate crown preparation was done by 24.2% while 75.8% have not done adequate preparation. Association of adequate preparation with practitioners showed that 8% general practitioners, 32% Postgraduates students and 54% consultants prepared crowns with adequate preparation which shows statistically significant association.Conclusion: It was concluded that adequate crown preparation standards were followed by consultants while general practitioners need to improve their skills for making proper fixed prosthesis preparation.